2020
DOI: 10.1158/1078-0432.ccr-20-1024
|View full text |Cite
|
Sign up to set email alerts
|

Population-based Screening for BRAFV600E in Metastatic Colorectal Cancer Reveals Increased Prevalence and Poor Prognosis

Abstract: Purpose: BRAF V600E mutations portend poor prognosis in metastatic colorectal cancer (mCRC); however, the true prevalence and prognosis are unknown, as unwell patients may not undergo BRAF sequencing.Experimental Design: We reviewed a population-based cohort of 1,898 patients with colorectal cancer that underwent reflexive IHC mismatch repair (MMR) and BRAF V600E testing. Outcomes among IHC-detected BRAF V600E mCRC (BRAF IHC ) were compared with patients with next-generation sequencing (NGS)-identified BRAF V6… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 19 publications
2
25
0
1
Order By: Relevance
“…Although there are mixed results around the use of FOLFOXIRI + bevacizumab for the first‐line treatment of BRAF V600E ‐mutated colorectal cancer in the recent meta‐analyses, it intuitively makes sense that one may want to use one's most aggressive option first, as these patients are prone to rapid deterioration and treatment attrition is high. A recent population‐based study showed that only 26% of patients with BRAF V600E ‐mutated colorectal cancer receive second‐line therapy [13].…”
Section: Who Is a Candidate For The Triplet Regimen?mentioning
confidence: 99%
“…Although there are mixed results around the use of FOLFOXIRI + bevacizumab for the first‐line treatment of BRAF V600E ‐mutated colorectal cancer in the recent meta‐analyses, it intuitively makes sense that one may want to use one's most aggressive option first, as these patients are prone to rapid deterioration and treatment attrition is high. A recent population‐based study showed that only 26% of patients with BRAF V600E ‐mutated colorectal cancer receive second‐line therapy [13].…”
Section: Who Is a Candidate For The Triplet Regimen?mentioning
confidence: 99%
“…Secondly, the number of patients with CRLM or LLM in our center was small, and thus, the results should be interpreted with caution. Thirdly, MMR or MSI status data were insufficient to analyze the mismatch repair system in patients with the BRAF V600E mutation; however, different survival outcomes were noted in advanced and mCRC with the BRAF V600E mutation [ 39 , 40 ]. Besides, in this cohort, we only identified one patient (1.1%) as dMMR, which is much lower than in western countries [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chu et al. investigated outcomes of immunohistochemical (IHC) and NGS testing in a cohort of almost 1900 CRC patients [ 65 ]. The rate of false-positive IHC tests was 17%; however, confirmatory re-testing by NGS was performed in only 43% of the IHC-tested patients.…”
Section: Braf Diagnosticsmentioning
confidence: 99%